SUPERVISION OF FIELD WORK PRACTICE FOR STUDENTS OF SHARIA BANKING STUDY PROGRAM, ISLAMIC UNIVERSITY OF DEPOK - Arnoldy, Arnoldy; Priyanto, Toni; Ibrahim, Ibrahim (Universitas Muhammadiyah Aceh, 2025)
Field Work Practice Program is a form of university community service aimed at bridging the gap (link and match) between education and industry. The goal of this activity is to provide students with experience in a professional work environment and to enhance technical competencies, soft skills, and teamwork needed by industry. This community service journal aims to examine lecturer mentoring during student Field Work Practice Program, with the aim of making the Field Work Practice Program process more focused and providing greater benefits in improving student competencies, soft skills, and teamwork. The Field Work Practice activities for students in the Sharia Banking Study Program at the Islamic University of Depok were conducted at the branch offices of several National Banks and Sharia Rural Bank (Bank Perekonomian Rakyat Syariah (BPRS)) in the Depok City area, involving sixth-semester students for one month in July and August 2025. The mentoring methods included initial briefing, observation, coaching, report writing, and evaluation of student learning performance. The results showed that the majority of students experienced improvements in their understanding of work processes, interdepartmental relationships, discipline, self-confidence, courage, adaptability and communication and teamwork skills. This Field Work Practice activity is considered effective as a means of helping improve the competency of university graduates who are ready to work.